Pengaruh Model Discovery Learning Berbasis Tugas Proyek Terhadap Hasil Belajar SMP Negeri 2 Tondano - Jeane Verra Tumangkeng; Djeli Tulandi (Chemistry Department, Universitas Negeri Manado, 2022)
This research was conducted with the aim to determine the effect of the use of project task-based discovery learning models on student learning outcomes in the subject of energy. This research was conducted on students of SMP Negeri 2 Tondano with a total of 23 students in each class. Class VII F uses the discovery learning model with project assignments and class VII G uses the discovery learning model without project assignments. The method used in this research is experimental research. The research design used was a posttest-only control design. In this design there are two classes, namely the experimental class and the control class. The experimental class is the class that is given treatment using the project task-based discovery learning model and the control class is the class that is given treatment using the discovery learning model without project assignments. The results showed that there was an effect of the use of project assignment-based discovery learning models on student learning outcomes in energy material at SMP Negeri 2 Tondano. The learning outcomes of students in class VII F who were taught using the project task-based discovery learning model were higher than those in class VII G who were taught using the discovery learning model without project assignments.